1. KETAHANAN PANGAN RUMAH TANGGA : REVIEW PASCA KENAIKKAN HARGA BBM - Subowo, Ari (Faculty of Social and Political Sciences Diponegoro University, 2009)
The question about households food stock after the increased price of fuel is remain debatable whilst it’s separated issue or it’s negative impact. Government perspective argued that by the increased price of fuel doesn’t any impact on it, while most non-government organization have strong statement that by the increased price of fuel is actually reluctant for household foodstock. This article will review how to measure household stock and follow by looking more deeper the households foodstock in order to review whether any changes after the increased price of fuel recently. Based on the review, the foodstock appears in the micro level have a serious impact on the decreasing the health nutrition status among households.